Evaluation of Knowledge and Attitude of Religious Affairs Office’s Staff in Conducting Reproductive Health Education for Prevention of Sexually Transmitted Infections in Premarital Couples - Muthia Sari; Yeva Rosana; Resti Hardianti Lestari; Aiman Idrus Alatas; Dimas Seto Prasetyo (Warta Pengabdian Andalas)
Sexually transmitted infections (STIs) are a significant public health challenge worldwide. Besides being transmitted through sexual intercourse, STIs can also be transmitted from mother to fetus during pregnancy, childbirth, and breastfeeding. Inadequate surveillance systems, community stigma, and limited access to health care hinder efforts to prevent STI transmission. Therefore, effective interventions are needed. This study aimed to increase the knowledge of the religious affairs office (KUA) staff about STIs and prevention of transmission so that KUA can become a partner to the community health center in providing counseling on healthy reproductive life to prospective couples. Participants were Cilandak KUA's staff and couples who came there. Activities included educational presentations, group discussions, and distribution of educational materials. Pre- and post-tests were conducted to measure the level of knowledge. Questionnaires were used to collect data on demographic characteristics, attitudes, and couple's willingness to undergo STI screening. The results showed an increase in the knowledge of couples and staff regarding STIs and prevention of transmission. Presentation by the doctor was the most effective method. This activity shows KUA's potency as a partner of a community health center in promoting STI prevention. However, ongoing support, training, and evaluation are needed to ensure that accurate information is consistently provided to the couples.